An inclusive odyssey grotesque and capacitism: about the artist and teacher Ana Amália (Palíndromo, 2023)
A photo-novel is presented here about the trajectory of the visual artist and teacher Ana Amália, who in 2002 suffered a stroke and became quadriplegic, mute and dysphagic. The objective of this photo-novela is to provoke reflections on ableism, since historically any type of disability has already been treated as grotesque, an issue she points out at the end. Because it is an artistic production, the qualitative research developed in a doctoral thesis carried out by her is associated with the artist's creative process, on which the narrative is structured. To this end, graphic and photographic resources are used with the same degree of importance as words, so that the many communication possibilities of a disabled person like Ana Amália can be perceived.
Keywords: people as a disability; capacitism; grotesque; visual arts; art/education